Representation of Pachakutiy in the poetry of César Guardia Mayorga - Mamani Macedo, Mauro (2017)
The epistemic colonization implies the imposition of foreign categories, which are external and distant. In other words, this action does not recognize the native culture and its forms of comprehension, classification and sensation. For this reason, we affirm that any culture has its words, its dictionary, its enciclopedia, its theoretical qipi to organize its knowledge. In this paper, we will study Pachakutiy, an Andean category; moreover we will verify its theoretical and hermeneutic scope in the literary interpretation. Firstly, we will propose a philological revision of the concept Pachakutiy. Secondly, we will use this category to analyze the poetry of César Guardia Mayorga. In this way, the visibilization of the alternation of times in his literary work will demonstrate the Pachakutiy's descriptive and analytic capacity.